Pomen reproduktivnega zdravstvenega varstva na primarni ravni - Andolšek-Jeras, Lidija (Zdravniški vestnik, 2003)
Background. The author discusses development and succcess of up to date reproductive health care provision of women at primary Level Health indicatorsshow 98% pregnant women attendency in prenatal care, 99% deliveries in maternity hospitals, figures comparable to the West European ones. Perinatal mortality (8/1000 livebirths) place Slovenia to the middle of the european scale. Infant mortality rate was reduced to 6/1000 livebirths and is very low compared to otherEuropean countries, while maternal mortality rate (27.6/100, 000 livebirths) is among the highest in Europe. Abortion rates are reduced to 16/1000 women of fertile age, mostly in the group of younger minors(2/1000), use of contraceptives (intrauterine device, hormonal contraceptive) is increasing. Due to increasing incidence of cervical cancer, the programme ZORA, active screening is organised. After 1992 Health reform the accessibility of reproductive health care provision is less favourable, restriction of reproductive rights is noticed, while the number of women who chose their personal gynecologist is progressing. In the article the author presents different views of the possible future development of reproductive health care provision at primary level.
Keywords: Abortion, Legal; Abortus legalni; Contraceptives, Oral, Hormonal; Dojenček, umrljivost; Infant Mortality; Kontracipiensi oralni, hormonski; Matere, zdravstvene službe; Maternal Health Services; Maternal Mortality; organizacija; organization; Osnovno, zdravstveno varstvo; Porodnice, umrljivost; Preventive Medicine; Preventivna medicina; Primary Health Care; Reproductive Medicine; reprodukcija; Reproduktivna medicina; woman; zdravstveno varstvo; ženske